Three new species of Tanytarsus van der Wulp (Diptera: Chironomidae) from the Amazon rainforest - Reis, Patricia Do Rosario; Lin, Xiao-Long; Ferreira-Keppler, Ruth L. (Zootaxa, 2022)
In the present study, three new species of Tanytarsus, collected in Brazilian Amazonia, are described and illustrated as adult males: T. pollicis sp. nov., T. marianae sp. nov. and T. rafaeli sp. nov. Tanytarsus pollicis is placed in kiche species group due to its bilobed superior volsella. Tanytarsus marianae and T. rafaeli are not placed in any known species group, and although these two new species share characters that suggest they may be closely related, we do not propose that they form a new species group for Tanytarsus without prior phylogenetic analysis.